Investigation on Waste Management Training Effectiveness on Community Behavior in Household Waste to Reduce the Waste Number Into the River in Penawar Village, Kerinci Regency - Hubaybah Hubaybah; Muhammad Izzan Naser; Fitria Eka Putri; Fajrina Hidayati; Vinna Rahayu Ningsih (Lembaga Pengembangan Kinerja Dosen, 2022)
Poor waste management can result in chemical exposure and health issues. With a %age of 42.63 %, Kerinci district is the district in Jambi province with the largest number of river trash disposals, while Penawar Village is the village with the highest number of river waste disposals. This study aims to investigate waste management training effectiveness on community behaviour in household waste to reduce the waste number into the river in Penawar village, Kerinci Regency. This research is a quasi-experimental study employing a pretest-posttest design group with a research sample of 46 houses and simple random sampling. The results showed that before the intervention, the majority of housewives' knowledge was lacking (34.8%), the majority attitude was negative (69.6%) and the majority action was poor (71.7%). After the implementation of the Household Waste Management Training, the majority of housewives' knowledge was good (89.1%), positive attitude (100%) and majority action was good (73.9%). Compared before intervention. The application of the training proved to be effective in increasing household waste management behavior with (p) < 0.05. Waste management training effectively enhances the knowledge, attitudes, and behaviors of housewives in managing home trash to lower the rate of garbage disposal into the river in Penawar Village, Kerinci Regency.